Intra- and interobserver reproducibility of pelvic ultrasound for the detection and measurement of endometriotic lesions. Issue 2 (6th March 2020) - Bean, E; Chaggar, P; Thanatsis, N; Dooley, W; Bottomley, C; Jurkovic, D
Abstract: STUDY QUESTION: What is the interobserver and intraobserver reproducibility of pelvic ultrasound for the detection of endometriotic lesions? SUMMARY ANSWER: Pelvic ultrasound is highly reproducible for the detection of pelvic endometriotic lesions. WHAT IS KNOWN ALREADY: Transvaginal ultrasound (TVS) has been widely adopted as the first-line assessment for the diagnosis and assessment of pelvic endometriosis. Severity of endometriosis as assessed by ultrasound has been shown to have good concordance with laparoscopy (kappa 0.79). The reproducibility of TVS for assessment of ovarian mobility and pouch of Douglas obliteration using the 'sliding sign' has already been described in the literature. However, there is no available data in the literature to demonstrate the intraobserver repeatability of measurements for endometriotic cysts and nodules. STUDY DESIGN, SIZE, DURATION: This was a prospective observational cross-sectional study conducted over a period of 12 months. We included 50 consecutive women who were all examined by two operators (A and B) during their clinic attendance. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study was carried out in a specialist endometriosis centre. We included all consecutive women who had ultrasound scans performed independently by two experienced operators during the same visit to the clinic. The outcomes of interest were the inter- and intraobserver reproducibility for the detection of endometriotic lesions. We also assessed repeatability of the measurements of lesion size. MAIN RESULTS AND THE ROLE OF CHANCE: There was a good level of agreement between operator A and operator B in detecting the presence of pelvic endometriotic lesions ( k  = 0.72). There was a very good level of agreement between operators in identifying endometriotic cysts ( k  = 0.88) and a good level of agreement in identifying endometriotic nodules ( k  = 0.61). The inter- and intraobserver repeatability of measuring endometriotic cysts was excellent (intra-class correlation (ICC) ≥ 0.98). There was good interobserver measurement repeatability for bowel nodules (ICC 0.88), but the results for nodules in the posterior compartment were poor (ICC 0.41). The intraobserver repeatability for nodule size measurements was good for both operators (ICC ≥0.86). LIMITATIONS, REASONS FOR CAUTION: Within this cohort, there was insufficient data to perform a separate analysis for nodule size in the anterior compartment. All examinations were performed within a specialised unit with a high prevalence of deep endometriosis. Our findings may not apply to operators without intensive ultrasound training in the diagnosis of pelvic endometriosis. WIDER IMPLICATIONS OF THE FINDINGS: These findings are important because ultrasound has been widely accepted as the first-line investigation for the diagnosis of pelvic endometriosis, which often determines the need for future investigations and treatment. The detection and measurement of bowel nodules is essential for anticipation of surgical risk and planning surgical excision. STUDY FUNDING/COMPETING INTEREST(S): The authors have no conflict of interest. No funding was obtained for this work.